2010
DOI: 10.1214/09-aos787
|View full text |Cite
|
Sign up to set email alerts
|

On the de la Garza phenomenon

Abstract: Deriving optimal designs for nonlinear models is in general challenging. One crucial step is to determine the number of support points needed. Current tools handle this on a case-by-case basis. Each combination of model, optimality criterion and objective requires its own proof. The celebrated de la Garza Phenomenon states that under a (p − 1)th-degree polynomial regression model, any optimal design can be based on at most p design points, the minimum number of support points such that all parameters are estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 19 publications
1
80
0
Order By: Relevance
“…Recently, Yang and Stufken (2009), Yang (2010), and Dette and Melas (2011) convincingly demonstrated that unifying results for multiple models, multiple optimality criteria and multiple objectives can be obtained in the context of nonlinear models. They show that we can focus on a subclass of designs with a simple form, no matter what type of optimal designs we are looking for, including optimal multi-stage designs.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, Yang and Stufken (2009), Yang (2010), and Dette and Melas (2011) convincingly demonstrated that unifying results for multiple models, multiple optimality criteria and multiple objectives can be obtained in the context of nonlinear models. They show that we can focus on a subclass of designs with a simple form, no matter what type of optimal designs we are looking for, including optimal multi-stage designs.…”
Section: Introductionmentioning
confidence: 97%
“…They obtain a series of excellent results, showing that under some conditions, for each given design there is always a design from a simple class which is better in the Statistica Sinica: Preprint doi: 10.5705/ss.2011.271 Loewner sense. These results were then generalised to models with more than two parameters by Yang (2010) and Dette and Melas (2011). Depending on the model, however, these conditions can be difficult to verify even using symbolic computational software.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the within-group information matrix does not share the desirable property of additivity as in traditional design problems, surprisingly it is still possible to identify complete class by the same way as in Theorem 1 in Yang (2010). This theorem shows that only a small number of support points are necessary to achieve optimal design under Model (2.5).…”
Section: Complete Class Of Within-group Designsmentioning
confidence: 96%